Oxidized Low-Density Lipoprotein Induces Reactive Oxygen Species-Dependent Proliferation of Intestinal Epithelial Cells - Eddy E. Gonzalez-Horta; Juan F. Burgueno; María J. Leiva; Carla Villavicencio; Fernando I. Kawaguchi; Hajar Hazime; Fátima Reyes; Viana Manrique-Suárez; Natalie C. Parra; Maria T. Abreu; Jorge R. Toledo (MDPI AG, 2024)
Background/Objectives: Oxidized low-density lipoprotein (ox-LDL) is a proinflammatory particle associated with various diseases and affects cell proliferation and viability in multiple cell types. However, its impact on intestinal epithelial cells remains underexplored. This study investigates the effect of ox-LDL on colonic epithelial cell proliferation and viability, as well as the underlying mechanisms involved. Methods: The expression levels of ox-LDL receptors in human colonoids were analyzed at baseline and in response to proinflammatory signals by qRT-PCR. The effect of ox-LDL on organoid proliferation was analyzed using morphometric measurements, viability assays, and the incorporation of a thymidine analog into DNA. The generation of reactive oxygen species (ROS) was determined by Amplex Red assays. Additionally, ox-LDL-induced ROS-dependent organoid proliferation was studied by exposing colonoids to an antioxidant or ROS inhibitors. Results: Colonic epithelial cells express ox-LDL receptors. Ox-LDL significantly induces the proliferation of colonic epithelial cells, which are dependent on ROS generation. Notably, ROS scavengers and NADPH inhibitors reduced ox-LDL-induced proliferation, highlighting the crucial role of oxidative stress in this process. Conclusions: This study demonstrates for the first time that ox-LDL stimulates CEC proliferation mediated by ROS production and validates that the colonic organoid model enables the analysis of potential pharmacological strategies for intestinal diseases characterized by oxidative stress and inflammation.